Blockchain-based Data Provenance - Lautert, Filipe; Pigatto, Daniel Fernandes Gonçalves; Gomes-JR, Luiz Celso (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2020: Anais do III Workshop em Blockchain: Teoria, Tecnologia e AplicaçõesDO - 10.5753/wblockchain.2020.12975, 2020)
Data provenance tracks the origin of information with the goal of improving trust among interested parties. One of the key aspects provided by data provenance is transparency, which allows stakeholders to follow all the changes applied to the information (e.g. a document). Blockchains, a recent technological development, allow transparency in a distributed application context without the need for a trusted centralized entity. The approach presented here aims to use blockchain as a secure, shared and auditable storage providing transparent data provenance. Our proposal builds upon the well established W3C Prov Model, which simplifies adoption of the framework. An application consisting of a client and a REST API service that is able to store provenance information using open standards in a blockchain has been developed. Here we report the results of several stress tests to validate the practicability of our approach.